Leader or Lobbyist? How Organizational Politics and Top Supply Chain Manager Political Skill Impacts Supply Chain Orientation and Internal Integration. Issue 4 (October 2016) - Thornton, LaDonna M.; Esper, Terry L.; Autry, Chad W.
Abstract : Despite myriad attempts by supply chain managers and exhortation by scholars, many firms remain insufficiently integrated across internal functional areas. Supply chain management research has hinted that the difficulty may be due to social dynamics occurring within and between organizational departments (i.e., organizational politics) and the perceptions thereof held by employees. This study examines whether perceptions of organizational politics held by firm employees negatively impact internal integration directly, or indirectly via inhibiting the firm's supply chain orientation. Based on social exchange theory and social influence theory, the research also assesses whether the potentially harmful impacts of political perceptions on internal integration are/can be mitigated by employees' perception of the political skill of the top supply chain management executive—a person charged with ensuring the firm's supply chain will function successfully. The findings of a broad managerial survey conducted within the U.S. retail industry suggest that perceptions of organizational politics within organizations do directly influence internal integration. Furthermore, the relationship between organizational politics and supply chain orientation is impacted when the top supply chain executive is perceived to be politically skilled.